THE EFFECT OF REGOSOL SOIL MIXED MEDIA, CHARCOAL POWDER AND MANURE ON THE SEEDLING GROWTH OF PINE (Pinus merkusii Jungher de Vrieser) - Marningot Tua Natalis Situmorang (Jurnal Perbenihan Tanaman Hutan, 2021)
This study aimed to determine whether mixed seedling media between regosol soil with manure and charcoal powder at various concentrations would affect seedlings growth of Pinus merkusii. This study used a completely randomized design (CRD) with six treatments and four replications: A: 100% regosol soil (control). B.: 50% regosol soil + 50% manure, C: 50 % regosol soil + 50% charcoal. D : 50% regosol soil + 25% manure + 25% charcoal, E: 25% regosol soil + 25% manure + 50% charcoal and F: 25% regosol soil +50% manure + 25% charcoal. The parameters measured were seedling height and diameter that carried out once every 10 days until harvest. After harvesting (60 days old seedling), the fresh weight, the total dry weight and the ratio of shoots to roots was calculated. Statistical analysis were carried out with Analysis of Variance and continued with Duncan's test at the 5% and 1% confidence levels. The results showed the growth of seedlings of P. merkusii planted on a mixture of 50% regosol soil + 25% manure + 25% charcoal (media D) resulted in a highest growth of the seedlings that is 4.35 cm, in average of height. The average diameter of the seedlings is 0.55 mm, the fresh weight of the seedlings is 0.220 g, the total dry weight of the seedlings is 0.035 g, and the ratio of shoots to roots of seedlings is 1,26.